2013
DOI: 10.1080/21622965.2013.802650
|View full text |Cite
|
Sign up to set email alerts
|

Relative Risk for Concussions in Young Female Soccer Players

Abstract: The objective of this study was to determine the relative risk and reported symptoms of concussions in 11- to 13-year-old, female soccer players. For this, a survey to compare the reported incidence of concussion in age-matched female soccer players to nonsoccer players was performed. The survey included 342 girls between the ages of 11 and 13: 195 were involved in an organized soccer team and 147 were not involved in organized soccer but were allowed to participate in any other sport or activity. A total of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
5
1
Order By: Relevance
“…A literature review of sex difference in sport concussion in high school, college, and professional levels likewise showed higher CRs for females compared to males in similar sports (Dick, 2009), a pattern that has been noted in several previous studies of high school athletes (Lincoln et al, 2011;Marar et al, 2012;Rosenthal et al, 2014). Possible explanations for sex differences in concussion patterns are limited, with some suggesting biomechanical (body mass, small head-to-ball ratio, neck strength), neuroanatomical, or hormonal factors underlying female concussions (Covassin, Swanik, & Sachs, 2003;Strand, Lechuga, Zachariah, & Beaulieu, 2015). Psychosocial influences may lead males to minimize injuries, play despite injury and underreport symptoms in order to continue to play (Kerr, Register-Mihalik, Kroshus, Baugh, & Marshall, 2016).…”
Section: Sexsupporting
confidence: 59%
“…A literature review of sex difference in sport concussion in high school, college, and professional levels likewise showed higher CRs for females compared to males in similar sports (Dick, 2009), a pattern that has been noted in several previous studies of high school athletes (Lincoln et al, 2011;Marar et al, 2012;Rosenthal et al, 2014). Possible explanations for sex differences in concussion patterns are limited, with some suggesting biomechanical (body mass, small head-to-ball ratio, neck strength), neuroanatomical, or hormonal factors underlying female concussions (Covassin, Swanik, & Sachs, 2003;Strand, Lechuga, Zachariah, & Beaulieu, 2015). Psychosocial influences may lead males to minimize injuries, play despite injury and underreport symptoms in order to continue to play (Kerr, Register-Mihalik, Kroshus, Baugh, & Marshall, 2016).…”
Section: Sexsupporting
confidence: 59%
“…We identified 5 studies that examined concussion-reporting behavior in female athletes. 6 , 22 , 38 , 45 , 53 Studies showed that a significant percentage of adolescent, 45 , 53 high school, 38 and collegiate athletes 6 , 22 failed to report concussion-like symptoms (CLS) and that many of these athletes returned to play with CLS ( Table 5 ). O’Kane et al 45 surveyed adolescent female soccer players over 4 years for the incidence of concussion.…”
Section: Resultsmentioning
confidence: 99%
“… 14 However, our review found that despite higher rates of reporting in female compared with male athletes, 57 underreporting still exists and leads to potentially untreated concussions. 6 , 22 , 38 , 45 , 53 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of sport is a predictor of risk of sport concussion. For example, young female soccer players aged 11-13 have 2 times the risk of sustaining a sport concussion compared to their non-sport and other-sport playing counterparts (Strand, Lechuga, Zachariah, & Beaulieu, 2014). However, this study assessed "probable" concussions, which makes this result less reliable.…”
Section: Sportmentioning
confidence: 99%